Micro Moments Database for Cross-Country Analysis of ICT, Innovation, and Economic Outcomes - Eric Bartelsman; Eva Hagsten; Michael Polder (Tinbergen Institute, 2017)
This paper provides technical documentation to a database built up from firm-level sources titled Micro moments database(MMD) that is made available for researchers through Eurostat. The MMD is an internationally harmonized research database of statistical moments collected from linked longitudinal firm-level data in a large selection of EU national statistical offices. The underlying sources for the database are business registers, firm-level surveys on production, usage of Information and Communications Technologies (ICT) and innovative activities, as well as recorded information on trade and worker education, all linked at the firm level. The unit of observation in the MMD represents groups of firms within industries and allows research that bridges micro and macro analysis. The paper delineates the type of research questions that uniquely can be addressed with the MMD, and the advantages and disadvantages of using MMD for questions where alternative datasets are available. The paper next presents the methodology underlying construction of the MMD and provides documentation of the rich set of features. Finally, the paper provides descriptive statistics that highlight the unique character of the data and reviews some of the cross-country analytical work already conducted using the MMD.
Keywords: D2; E2; F1; J2; L2; O3; 330; Innovation; ICT; Productivity; Intangible Investment; linked firm-level datasets